Metode System Development Life Cycle dalam Perancangan Sistem Informasi Kuliah Kerja Kemasyarakatan - Hidayat, Taufik; Mobarrok, Abi; Sukisno, Sukisno; Nugroho, Asep Hardiyanto (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Our annual activity, Community Service Internship, will be conducted this semester. Previously, this reporting activity was carried out by sending pictures via WhatsApp. So, we created a reporting system to make it more efficient. Now, the reporting process will be handled through a website and monitoring will also be done through the website. This will make it easier for both participants and mentors to carry out the activity," he said. The methodologies used are SDLC (System Development Life Cycle) for documentation and Prototype methodology for system design. ISO 9126 has been used for system testing with a functionality score of 84% and a usability score of 89.45%. So, from testing to system design to documentation, everything was done as per the requirements.